Anti-Allergic Inflammatory Effect of Agarum cribrosum and Its Phlorotannin Component, Trifuhalol A, against the Ovalbumin-Induced Allergic Asthma Model - Kim, Joonki; Lee, Sang Heon; Zhang, Siqi; Bong SimKyu; Kim, Aaron Taehwan; Lee, Hara; Liu, Xiaoyong; Kim, Sang Moo; Kim, Su-Nam (MDPI, 2023)
Asthma is a chronic inflammatory disease involving structural changes to the respiratory system and severe immune responses mediated by allergic cytokines and pro-inflammatory mediators. Agarum cribrosum (AC) is a kind of seaweed which contains a phlorotannin, trifuhalol A. To evaluate its anti-allergic inflammatory effect against asthma, an ovalbumin inhalation-induced mouse asthma model was used. Histologic observations proved that trifuhalol A is minimizing the lung and tracheal structure changes as well as the infiltration of eosinophils and mast cells against ovalbumin inhalation challenge. From the serum and bronchoalveolar lavage fluid, ovalbumin-specific IgE and Th2-specific cytokines, IL-4, -5, and -13, were reduced with trifuhalol A treatment. In addition, IL-1β, IL-6, and TNF-α concentrations in lung homogenate were also significantly reduced via trifuhalol A treatment. Taken together, trifuhalol A, isolated from AC, was able to protect lung and airways from Th2-specific cytokine release, and IgE mediated allergic inflammation as well as the attenuation of IL-1β, IL-6, and TNF-α in lung, which results in the suppression of eosinophils and the mast cells involved asthmatic pathology.